EPIDEMIOLOGICAL CORRELATES OF POSTMENOPAUSAL BLEEDING IN A TERTIARY CARE HOSPITAL - Arora, Sonia; Anand, Bhupinder Kaur; Marwaha, MPS; Singh, Abha (Indian Journal of Community Health, 2012)
Background: A woman is considered menopausal after 12 months of amenorrhea. The most feared symptom during menopause is postmenopausal bleeding which unless proved otherwise indicates genital malignancy. Objectives: To study Socio-demographic factors related to postmenopausal bleeding and to find time lapse between bleeding and reporting of these cases. Material and Methods: This cross sectional was done in the Department of Obstetrics & Gynecology, Pt. J. N. M. Medical College & DR. B. R. Ambedkar Memorial, Hospital, Raipur (C. G.) The participants were 146 women who came with the complaint of postmenopausal bleeding. A detailed, preceded, pre-tested, structured, close ended questionnaire was used to collect the data. By interviewing these women, information was collected about different demographic factors like age, socio-economic status, parity etc. The collected data was put in the master chart and analyzed. Results: The proportion of postmenopausal bleeding cases was 3.5% .Maximum cases(50%) with postmenopausal bleeding were found in the age group of 45-54yrs . 60 % of patients were from rural areas and 62% were illiterate. 65% of the patients were grand multipara (Parity4). Most of the patients belonged to lower socioeconomic strata. Almost half (48%) of patients presented after, more than 6 months since the first episode of bleeding . Conclusions: The proportion of postmenopausal bleeding is high, requiring immediate investigation. Lack of awareness led to very late presentation of most of the patients, so education at community level is required to reduce this time lapse for earlier diagnosis and management